Past COVID-19 infection and feasibility of transcatheter aortic valve replacement in a patient with severe aortic stenosis (a clinical case study) - O. A. Zemlyanskaya; E. V. Kurilina; E. P. Panchenko («REMEDIUM GROUP» Ltd., 2022)
A fatal case of severe stenosis of the aortic orifice in a patient with not diagnosed in time, long-term persistent covid infection is presented. The patient was hospitalized to resolve the issue of surgical correction of the aortic stenosis. On admission, there were symptoms of circulatory failure at the level of 3-4 functional class according to NYHA and angina pectoris clinic. A detailed collection of anamnesis about the epidemiological environment and symptoms of pneumonia suffered in the fall of 2020 raised suspicions of its covid genesis. Subsequently, this assumption was confirmed by the data of laboratory, instrumental studies, as well as the results of the pathological and anatomical autopsy. The study of microslides showed signs of extensive vasculitis with thrombosis of small branches of the pulmonary artery and foci of pneumofibrosis of various degrees of prescription, which also testified in favor of the transferred covid infection. Taking into account the severity of the patient's condition upon admission, it was not possible to perform emergency intervention on the aortic valve. After stabilization of the state and regression of the phenomena of circulatory failure, it was planned to simultaneously perform endovascular revascularization of the coronary valve bed and transcatheter aortic valve replacement. The planned surgical intervention failed. The immunosuppressive effect of the SARS-CoV-2 virus, apparently, led to the activation of autoflora and an increase in inflammation for nosocomial infection. Bilateral polysegmental bacterial pneumonia that joined during hospitalization, against the background of postcoid changes in the lung parenchyma, contributed to the development of acute coronary syndrome with ventricular arrhythmias. The patient died from acute cardiopulmonary failure. The article also presents ideas about the operational tactics of managing patients with aortic stenosis in a pandemic.